The use of two non-toxic lipophilic oils to generate environmentally friendly anionic reverse micelles without cosurfactant. Comparison with the behavior found for traditional organic non-polar solvents - Girardi, Valeria Romina (2014)
In this work two different non-toxic solvents/sodium 1,4-bis-2-ethylhexylsulfosuccinate (AOT)/water reverse micelles (RMs) have been investigated by dynamic (DLS) and static (SLS) light scattering techniques. Methyl laurate (ML) and isopropyl myristate (IPM) were used as external non-polar solvents to formulate the AOT RMs without cosurfactant. DLS results reveal the formation of IPM and ML AOT RMs containing water as a polar component since the droplet sizes values increase as the W0 values increase. To the best of our knowledge this is the first report where ML is used to formulate AOT RMs. The droplets size values, the maximum amount of water solubilized and the aggregation numbers (Nagg, determined by SLS) of both AOT RMs are dissimilar considering the chemical structure of the external solvents and they can be explained taking into account the different non-polar solvent penetration to the interface. The results suggest that IPM penetrate more the interface than ML in AOT RMs, diminishing the interdroplets interactions and producing RMs with smaller sizes and Nagg than ML/AOT. The higher viscosity and polarity of IPM in comparison with ML promotes the interface penetration. Thus, the penetration of IPM into the interface is higher than ML, making the interface of IPM/AOT RMs more rigid and, in consequence with smaller droplets sizes values. Finally, a peculiar comparable behavior (droplets size, maximum amount of water solubilized and Nagg) between n-heptane and ML AOT RMs and benzene and IPM AOT RMs was observed. These results present a very promissory field since that the unique properties of the alkanes/AOT/water RMs can be obtained using non-toxic lipophilic oils and, in the same way the opportunity to formulate environmentally friendly AOT RMs.